PCV23 Depression and Coronary Heart Disease Risk: An Overview of Systematic Reviews (2016)
Relation between depression as risk factor for cardiovascular diseases remains as a controversial subject in therapeutics. The aim of this study was to assess the association of the depression as a risk factor for coronary heart disease (CHD) based on prospective studies included in published systematic reviews